THEORETICAL FOUNDATIONS FOR THE FORMATION OF THE INFORMATIONAL-RESEARCH COMPETENCE OF THE BASIC SCHOOL STUDENTS THROUGH WORKING WITH EDUCATIONAL TEXTS - Myrzashova Alua Elshatovna; Kaliyeva Kulyanda Makhambetzhanovna (Theoretical Hypotheses and Empirical Results, 2025)
In the current educational context, special attention is given to the development of competences that enable students to independently navigate the information space, critically interpret data, and apply it in research activities. A key role in this process is played by the informational-research competence, which is understood as a combination of knowledge, skills, and abilities aimed at the independent search, analysis, and interpretation of information [1]. According to I.A. Zimnyaya, the development of the informational-research competence is closely linked to students’ cognitive activity and the formation of key competences, among which communicative and cognitive competences play a special role [2]. Research by V.I. Savinkov also confirms that the informational-research competence is essential for developing independence and critical thinking in schoolchildren, and N.G. Makhmutov points to the importance of problem-based learning in shaping research skills [3, p.56]. In this context, English language education acquires special importance, as it is not only a means of international communication but also a tool for working with global informational resources. As noted by N.D. Galskova and N.I. Gez, learning a foreign language involves not only mastering lexical and grammatical material but also developing the ability to work with textual information, analyze it, and interpret it [4, p.12]. In this sense, educational texts are an important tool for fostering students’ research activity, as emphasized in the works of I.N. Vereshchagina and T.Y. Pritykina [5, p.34].